1990
DOI: 10.1002/pros.2990170402
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of muscarinic cholinergic receptors in membrane preparations from rat prostatic adenocarcinoma

Abstract: The binding characteristics of 3H-quinuclidinyl benzilate (QNB) to muscarinic sites in isolated plasma membrane fractions from R-3327 Dunning tumors (H and AT-1 sublines); ventral, dorsolateral prostate; and urinary bladder of the rat were studied. QNB binding to all preparations, except from AT-1 tumors, was specific, saturable, and of high affinity. The AT-1 tumors completely lacked specific QNB binding. The muscarinic receptor density in H tumors was twofold and twentyfold higher than that in the ventral pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…As shown in Table 1, muscarinic receptor expression is reported in tissues and cell lines derived from cancer of the brain (58) lung (114,115), ovary (93), pancreas (2,116), prostate (8,84), skin (15,16,108), stomach (76), and uterus (116). Nonetheless, because muscarinic receptor expression is common if not ubiquitous in all tissues, simply demonstrating expression of muscarinic receptors is insufficient to conclude that muscarinic signaling plays an important role in cancer progression.…”
Section: Proposed Criteria To Validate Muscarinic Receptor-mediated Amentioning
confidence: 92%
See 1 more Smart Citation
“…As shown in Table 1, muscarinic receptor expression is reported in tissues and cell lines derived from cancer of the brain (58) lung (114,115), ovary (93), pancreas (2,116), prostate (8,84), skin (15,16,108), stomach (76), and uterus (116). Nonetheless, because muscarinic receptor expression is common if not ubiquitous in all tissues, simply demonstrating expression of muscarinic receptors is insufficient to conclude that muscarinic signaling plays an important role in cancer progression.…”
Section: Proposed Criteria To Validate Muscarinic Receptor-mediated Amentioning
confidence: 92%
“…In prostate adenomas, Lepor and Kuhar (79) initially described and Ruggieri et al (107) classified muscarinic receptors. Muscarinic receptors are expressed in both rat and human prostate cancer cell lines (8,84). In 1997, Rayford et al (104) reported that carbachol stimulates prostate cancer cell proliferation, an action attenuated by addition of muscarinic receptor inhibitors.…”
Section: Prostate Cancermentioning
confidence: 98%
“…With regard to parasympathetic cholinergic mechanisms, stimulation of muscarinic receptors of the M 3 subtype have been shown to stimulate proliferation of LNCaP prostate cancer cells as well as benign and cancerous primary prostate cells 135 . Similarly, in studies of the cancerous rat prostate, an increase in M 3 muscarinic receptor density was observed 136 . This suggests that M 3 muscarinic receptors may play a significant role in prostate cancer tumor growth and possibly also androgen-independent tumor progression.…”
Section: Prostate Cancermentioning
confidence: 95%
“…Acetylcholine has previously been shown to have a strong hyperpolarizing influence in lacrimal [60] and parotid [61] gland cells, mainly through activation of K þ conductances. Muscarinic receptors (m3 subtype) have been localized both in the stroma and epithelia of the prostate gland [35] and are also expressed in rat prostate cancer cell lines [62]. Sympathetic cholinergic nerves exhibit an intimate spatial association with the glandular epithelium of the prostate [63] and muscarinic agonists directly stimulate cellular secretion in the gland [15].…”
Section: Acetylcholinementioning
confidence: 99%